Isolating America - Baker, Glenn (Washington : Center for Defense Information, 2000)
Against the tide of globalization, America is becoming increasingly isolationist. Congress' rejection of the Nuclear Weapons Test Ban Treaty was but the latest episode in a trend toward'Fortress America' that includes rejection of treaties on landmines and child soldiers, and a perennial failure to pay U.S. dues to the United Nations. The public is right to ask whether major increases in military spending for programs like ballistic missile defense and hi-tech fighter planes are a better investment in the long run than fostering regional peace initiatives, helping our former enemies become democratic friends, and using diplomacy to help prevent conflicts.
Scriptwriter, Glenn Baker
Narrator: Lisa Simeone
Keywords: United States, Army -- History -- 20th century